Toll-like receptor signalling on Tregs: to suppress or not to suppress? - van Maren, Wendy W C (Blackwell Science Inc, 2008)
To balance self-tolerance and immunity against pathogens or tumours, the immune system depends on both activation mechanisms and down-regulatory mechanisms. Immunologists have long been focusing on activation mechanisms, and a major breakthrough was the identification of the Toll-like receptor (TLR) family of proteins. TLRs recognize conserved molecular patterns present on pathogens, including bacteria, viruses, fungi and protozoa. Pathogen recognition via TLRs activates the innate as well as the adaptive immune response. The discovery of a suppressive T-cell subset that constitutively expresses the interleukin (IL)-2 receptor α-chain (CD25) has boosted efforts to investigate the negative regulation of immune responses. It is now well appreciated that these regulatory T cells (Tregs) play a pivotal role in controlling immune function. Interestingly, recent studies revealed that TLR2 signalling affects Treg expansion and function. This review will focus on the presence and influence of different TLRs on T lymphocytes, including Tregs, and their role in cancer.